PENGARUH FAKTOR INTERNAL, EKSTERNAL DAN MOTIVASI DAN TERHADAP MINAT BERWIRAUSAHA PADA MAHASISWA JURUASAN AKUNTANSI (Studi Mahasiswa STIE Malangkucecwara Malang) - Purwanto, Nanang; Sugiono, Djoko (DINAMIKA DOTCOM, 2017)
The economic crisis that plagued our country caused the business world has been so sharp decline. This has an impact on the working world that continues to narrow and the community continues to need work. For that, we need a settlement with this problem is to create jobs with entrepreneurship. Students as one of human resources have a big role in creating jobs so thatunemployment can be solved well. For that need to be considered internal factors, external, motivation and interest in entrepreneurship. The population in this study are students majoring in Accounting STIE Malangkucecwara Malang, with data collection method is a questionnaire and analysis method using multiple regression